Sufi interpretation in Islam: History, limitations, influences, and criticisms - Saufa, Syifa Nur; Shofiyah, Siti (Jurnal Iman dan Spiritualitas, 2025)
In every era, the interpretation of the Qur'an reflects a diversity of approaches, depending on the scholarly expertise of the interpreters (mufassir). One distinctive interpretative pattern is Sufi exegesis, despite its limited development due to challenging sceptical views. This research aims to address inquiries regarding the scope of Sufi exegesis, encompassing its historical emergence, limitations, differences in scholars' perspectives, and the terms "nazhari" and "ishari" Sufi exegesis. Employing qualitative methods and literature review, this study aligns expert views to achieve a nuanced understanding. The conclusion reveals that Sufi exegesis has deep-rooted origins since the early days of Islam, contributing to the development of Islamic spirituality and intellectual heritage. Despite its significance, critiques of symbolic and allegorical approaches raise questions about the clarity and certainty of Sufi interpretation. Research recommendations emphasize a more in-depth examination of empirical approaches in Sufi exegesis, integrating Sufi aspects with robust scientific methods, and exploring their social and moral impact in contemporary Muslim societies.